The Delphi and GRADE methodology used in the PSOGI 2018 consensus statement on Pseudomyxoma Peritonei and Peritoneal Mesothelioma. Issue 1 (January 2021) - Lurvink, R.J.; Villeneuve, L.; Govaerts, K.; de Hingh, I.H.J.T.; Moran, B.J.; Deraco, M.; Van der Speeten, K.; Glehen, O.; Kepenekian, V.; Kusamura, S.; ,; Alyami, Mohammad S.; et al.
Abstract: Pseudomyxoma Peritonei (PMP) and Peritoneal Mesothelioma (PM) are both rare peritoneal malignancies. Currently, affected patients may be treated with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy offering long-term survival or even cure in selected patients. However, many issues regarding the optimal treatment strategy are currently under debate. To aid physicians involved in the treatment of these patients in clinical decision making, the PSOGI executive committee proposed to create a consensus statement on PMP and PM. This manuscript describes the methodology of the consensus process. The Delphi technique is a reliable method for attaining consensus on a topic that lacks scientific evidence through multiple voting rounds which feeds back responses to the participants in between rounds. The GRADE system provides a structured framework for presenting and grading the available evidence. Separate questionnaires were created for PMP and PM and sent during two voting rounds to 80 and 38 experts, respectively. A consensus threshold of 51.0% was chosen. After the second round, consensus was reached on 92.9%–100.0% of the questions. The results were presented and discussed in the plenary session at the PSOGI 2018 international meeting in Paris. A third round for the remaining issues is currently in progress. In conclusion, using the Delphi technique and GRADE methodology, consensus was reached in many issues regarding the treatment of PM and PMP amongst an international panel of experts. The main results will be published in the near future.